2021
DOI: 10.1101/2021.05.14.444185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Label-free super-resolution chemical imaging of biomedical specimens

Abstract: Raman microscopy provides chemically selective imaging by exploiting intrinsic vibrational properties of specimens. Yet, a fast acquisition, low phototoxicity, and non-specific (to a vibrational/electronic mode) super-resolution method has been elusive for tissue imaging. We demonstrate a single-pixel-based approach, combined with robust structured illumination, that enables fast super-resolution in stimulated Raman scattering microscopy at low power levels. The methodology is straightforward to implement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Our results demonstrate the power of Raman imaging, particularly over other popular optical imaging methods such as reflection/scattering microscopy, for providing label-free microscopic chemical information especially in material science applications. Combining such techniques with super-resolution 53,54 or tip-enhanced [55][56][57] approaches will allow access to the sub-100 nm resolution limit and broaden the set of systems that can be examined, e.g. polymer ABSs and phase separations at electrified interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate the power of Raman imaging, particularly over other popular optical imaging methods such as reflection/scattering microscopy, for providing label-free microscopic chemical information especially in material science applications. Combining such techniques with super-resolution 53,54 or tip-enhanced [55][56][57] approaches will allow access to the sub-100 nm resolution limit and broaden the set of systems that can be examined, e.g. polymer ABSs and phase separations at electrified interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the time-resolution of Raman (imaging) will allow faster scan rates to be explored and using optically or electronically-gated methods 18,42 it may even be possible to probe pico-to nanosecond processes such as electron-transfer and ion (de)solvation 43 . Enhancing the spatial resolution of Raman imaging with near-field 44 or super-resolution 45,46 methods will further aid answering of such questions. Automation to allow scanning over large numbers of particles and correlation with complementary techniques such as X-Ray imaging/TEM 14,47 will be key to further enhance the utility of such methods 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one report has shown noninvasive focusing using highly sparse samples (therefore focusing convergence is guaranteed) [94], highlighting the need to develop tools for deep Raman imaging, although recent work has shown that variance-based computational methods allow for 'chemical' focusing using wavefront shaping [88]. Finally, speckles have been used to enable super-resolution in Raman-based processes [95], opening another research venue for exploiting computational tools in deep imaging.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%